2017
DOI: 10.1038/srep43421
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in A-to-I RNA editing patterns in CNS injuries correlate with dynamic changes in cell type composition

Abstract: Adenosine to Inosine (A-to-I) RNA editing is a co- or post-transcriptional mechanism that modifies genomically encoded nucleotides at the RNA level. A-to-I RNA editing is abundant in the brain, and altered editing levels have been reported in various neurological pathologies and following spinal cord injury (SCI). The prevailing concept is that the RNA editing process itself is dysregulated by brain pathologies. Here we analyzed recent RNA-seq data, and found that, except for few mammalian conserved editing si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…This could be due to the greater variability in cell populations (e.g., neurons vs. astrocytes, or pyramidal cells vs. interneurons) in the PFC at this early developmental stage. Since RNA editing levels can vary as a result of cell type composition [ 81 ] and since the Htr2c plays an important role in neurodevelopment [ 72 ], future studies should examine A and B site editing in distinct cell populations during development.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the greater variability in cell populations (e.g., neurons vs. astrocytes, or pyramidal cells vs. interneurons) in the PFC at this early developmental stage. Since RNA editing levels can vary as a result of cell type composition [ 81 ] and since the Htr2c plays an important role in neurodevelopment [ 72 ], future studies should examine A and B site editing in distinct cell populations during development.…”
Section: Discussionmentioning
confidence: 99%
“…While there are more protein recoding editing events in flies than in mammals, a number of mammalian ion channels also undergo functionally important RNA editing events, some of which are dynamically regulated across brain tissues in multiple species 18,19 ; yet, elucidating the function of a particular editing site may not be fully assessed at the entire tissue level. Editing levels are known to differ between neurons and glial cells 20 , but little is known about the diversity and the functional importance of this process in different neuronal populations. So far, RNA editing profiling of Drosophila neurons faced technical difficulty of reliably defining and isolating certain neuronal populations out of many in sufficient quantity, and thus editing level measurements typically represent an average of editing from large brain regions or whole brain tissue.…”
Section: Studies Indicate That Editing Modulates the Kinetics Of The mentioning
confidence: 99%
“…Recent analyses also suggested that newly originated A-to-I RNA editing events are generally selectively constrained ) and edited As have a relatively high fitness (Popitsch et al 2017). Accumulating evidence indicates that RNA editing is crucial in the neuronal dynamic in the mammalian central nervous system (Gal-Mark et al 2017). A handful of editing events have been demonstrated to be highly regulated during brain development or neural differentiation (Barbon et al 2003;Kawahara et al 2004;Wahlstedt et al 2009;Osenberg et al 2010) and involved in neuronal diseases, such as inflammation, epilepsy (Brusa et al 1995;Srivastava et al 2017), depression (Gurevich et al 2002), and amyotrophic lateral sclerosis (ALS) (Hideyama et al 2012).…”
Section: Discussionmentioning
confidence: 99%